2002
DOI: 10.1352/0895-8017(2002)107<0361:padiat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Dietary Intake, and the Insulin Resistance Syndrome in Nondiabetic Adults With Mental Retardation

Abstract: The association between physical activity, dietary behaviors, and elevated cardiovascular disease risk factor components of the insulin resistance syndrome in adults with mental retardation was identified. Established clinical cutoff points were used to identify 145 participants with mild mental retardation and hyperinsulinemia, borderline high triglycerides, low high-density lipoprotein cholesterol, hypertension, and abdominal obesity. Odds ratios were calculated from logistic regression analysis. Those who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…40,41,45,55,68 Comorbid conditions such as obesity or endocrine disorders that require nutrition interventions are also more likely to develop as the population ages. 22 Poor nutrition-related health habits, limited access to services, and long-term polypharmacy are considered significant health risk factors.…”
Section: Person-centered Languagementioning
confidence: 99%
“…40,41,45,55,68 Comorbid conditions such as obesity or endocrine disorders that require nutrition interventions are also more likely to develop as the population ages. 22 Poor nutrition-related health habits, limited access to services, and long-term polypharmacy are considered significant health risk factors.…”
Section: Person-centered Languagementioning
confidence: 99%
“…Studies have shown that people with intellectual disabilities have a high prevalence of overweight and obesity (Rimmer & Wang, 2005;Yamaki, 2005). Several factors may contribute to this pattern, including living in community versus institutional settings (Krauss & Seltzer, 1986;Janicki & Jacobson, 1986;Levy et al, 2006); engaging in high-risk behaviors, such as adopting poor diets and physical activity patterns (Pitetti, Rimmer, & Fernhall, 1993;Draheim, McCubbin, & Williams, 2002;Draheim, Williams, & McCubbin, 2002a;Draheim, Williams, & McCubbin, 2002b); and being treated with certain psychotropic medications (Spreat, Conroy, & Fullerton, 2004). However, few studies have explored these and other clinical and behavioral characteristics as potential risk factors for obesity and CHD in samples of people with ID with different levels of intellectual impairment and origin of impairment (Merriman, Haw, Kirk, & Stubbs, 2005;Draheim et al, 2002).…”
Section: Abstract Cardiovascular Disease Obesity Primary Carementioning
confidence: 99%
“…Other studies also showed improvements in muscle strength following training programmes for individuals with Down syndrome [19,20] . Draheim REPORTS bin [50] found reduced risk of hyperinsulinemia and abdominal obesity in adults with mental retardation (with and without Down syndrome) who were moderately to vigorously physically active at least five days per week and consumed lower dietary fat intakes. Together, these studies suggest that physical activity or exercise training can increase physical fitness in individuals with Down syndrome.…”
Section: Benefits From Physical Activity or Exercisementioning
confidence: 99%